Granting Greater Municipality Status in Turkey: Issues, Policy Process and Outcomes - Huseyin Ozgur (European Regional Science Association (ERSA), 2006)
The main objectives of this paper are to question the criteria and establishment process of granting greater municipality status and to develop comprehensive and precise criteria and procedures for major Turkish urban regions. Currently, 16 greater (metropolitan) municipalities exist in Turkey in addition to 3200 other municipalities. All these greater municipalities were established by the Turkish Parliament based on the previous Act of 1984, which stayed in force until 2004. According to 1984 Greater Municipalities Act, major criteria were economic and social development level, which were to be assessed by the Government. However, social and economic development indicators were never established for such an assessment and decision for granting all current greater municipalities were made by the general political considerations and rough assumptions about the need and suitability of those urban areas. Only 5 of the greater municipalities' population exceed 1 million, and still 5 of them are under 500.000 according to 2000 Census. Considering the lack of certain reasonable criteria for gaining greater municipality status, almost 15 other major (populous) municipalities with the population of around 500.000, have searched various ways and made several attempts to be granted greater municipality status by the Turkish Parliament. However, with the exception of Adapazarý (in 2000), all the greater municipalities were granted their status between 1984 and 1993. The exception for Adapazarý urban area was done due to major earthquakes in the Marmara Region in 1999. Yet, those other major urban areas having metropolitan characteristics are still waiting for being granted greater municipality status. The 2004 Act brings a new criterion, which requires settlements in a 10km diameter to have a minimum of 750.000 populations, which not based on academic and practical arguments. Ambiguously, economic and social development criteria are still effective in 2004 Act. However, middle-sized urban areas whose populations are around 500.000 and struggling for greater municipality status left administratively fragmented, and continue their existence being deprived of status, prestige, power, strong financial resources, administrative structure which greater municipality status may provide. Thus, determining precise criteria and processes for granting greater municipality status is an urgent and vital policy area in Turkish local government system. After summarizing the evolution of Turkish greater municipality system, this paper discusses establishing alternative and comprehensive criteria for granting greater municipalities in Turkey in a wider context of international literature and similar cases in European urban regions.
Keywords: 330